Manganese‐Catalyzed Carbonylative Annulations for Redox‐Neutral Late‐Stage Diversification. (6th April 2018) - Liang, Yu‐Feng; Steinbock, Ralf; Münch, Annika; Stalke, Dietmar; Ackermann, Lutz
Abstract: An inexpensive, nontoxic manganese catalyst enabled unprecedented redox‐neutral carbonylative annulations under ambient pressure. The manganese catalyst outperformed all other typically used base and precious‐metal catalysts. The outstanding versatility of the manganese catalysis manifold was reflected by ample substrate scope, setting the stage for effective late‐stage manipulations under racemization‐free conditions of a wealth of marketed drugs and natural products, including alkaloids, amino acids, steroids, and carbohydrates.